Left ventricular stroke volume calculation based on Reuleaux triangle formula: correct geometric characteristics of aortic root in systemic blood flow assessment - A. B. Naumov; V. V. Makaruk; S. P. Marchenko; O. Yu. Chupaeva; A. M. Volkov; G. G. Khubulava (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to estimate the left ventricular stroke volume calculated using the Reuleaux triangle formula, and compare with the parameters obtained from measurements in the left ventricle outflow tract. METHODS AND MATERIALS. A prospective cross-sectional study of the dimensions of the left ventricular outflow tract (LVOT), the aortic valve, and the velocity-time integral (VTI) was carried out, followed by calculation of the left ventricular stroke volume in the LVOT and aortic valve in 36 patients receiving renal replacement therapy.  RESULTS. The sizes of anatomical structures were determined in 36 patients. The average value of the LVOT area was calculated – 3.8 cm2, the average value of the area of the aortic valve (AV) opening was 2.8 cm2, the AV area according to the circle formula – 3.14 cm2, the AV area according to the Reuleaux triangle formula – 2.8 cm2. The mean value of the VTI in the LVOT was 21 cm; the VTI on the AV was 26.9 cm. The stroke volume (SV) in the LVOT was 70.85 ml, the SV on the AV by the area of the AV opening was 70.9 ml, the SV on the AV according to the circle formula – 76.5 ml, SV for AV according to the Reuleaux triangle formula – 68.72 ml. In a comparative analysis of the results of mathematical calculations, it was revealed that, in comparison with the SV in LVOT, the discrepancy between the results was more than 30 % when using the circle formula (χ2=4.1, p=0.04), in comparison with the Reuleaux triangle formula (13.8 % versus 4.1 %, respectively).  CONCLUSION. Parameters of the left ventricular stroke volume calculated with the Reuleaux triangle formula matches to the reference values selected in the study, calculated for the left ventricular outflow tract.